2013
DOI: 10.1371/journal.pone.0076791
|View full text |Cite
|
Sign up to set email alerts
|

Co-Overexpression of GEP100 and AMAP1 Proteins Correlates with Rapid Local Recurrence after Breast Conservative Therapy

Abstract: A major problem of current cancer research and therapy is prediction of tumor recurrence after initial treatment, rather than the simple biological characterization of the malignancy and proliferative properties of tumors. Breast conservation therapy (BCT) is a well-approved, standard treatment for patients with early stages of breast cancer, which consists of lumpectomy and whole-breast irradiation. In spite of extensive studies, only 'age' and 'Ki-67 positivity' have been identified to be well correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Our previous study, in which we examined the expression of AMAP1 and GEP100 by immunohistochemistry, demonstrated that co-overexpression of these 2 proteins exhibits a tight correlation with rapid local recurrence after breast conservative therapy, indicating that the ARF6-based pathway plays a central role in recurrence. 9 In accordance with this result, a recent report showed that the recurrence rates of breast cancer can be reduced by statins. 10 Other types of cancers, such as lung adenocarcinomas and head and neck squamous cell carcinomas, also overexpress the ARF6-based pathway (see refs.…”
supporting
confidence: 55%
“…Our previous study, in which we examined the expression of AMAP1 and GEP100 by immunohistochemistry, demonstrated that co-overexpression of these 2 proteins exhibits a tight correlation with rapid local recurrence after breast conservative therapy, indicating that the ARF6-based pathway plays a central role in recurrence. 9 In accordance with this result, a recent report showed that the recurrence rates of breast cancer can be reduced by statins. 10 Other types of cancers, such as lung adenocarcinomas and head and neck squamous cell carcinomas, also overexpress the ARF6-based pathway (see refs.…”
supporting
confidence: 55%
“…40 An Arf6 pathway, which employs ASAP1 as its effector, activates b1 integrins and perturbs E-cadherin-based adhesion; hence it appears to be integral for EMT. 41 These results suggest that h-prune and its binding partner might be involved in activation of EMT.…”
Section: Discussionmentioning
confidence: 85%
“…Conversely, ASAP1 is a metastasis‐promoting factor that interacts with h‐prune and stimulates its phosphodiesterase activity, and it is associated with increased tumor cell motility and invasiveness in vitro . An Arf6 pathway, which employs ASAP1 as its effector, activates β1 integrins and perturbs E‐cadherin‐based adhesion; hence it appears to be integral for EMT . These results suggest that h‐prune and its binding partner might be involved in activation of EMT.…”
Section: Discussionmentioning
confidence: 95%
“…We showed that overexpression of ASAP1 promoted EMT in both SKOV3 and OVCAR3 cells, indicating that ASAP1 may contribute to tumor metastasis and chemoresistance in ovarian cancer cells. Although it is not clear how ASAP1 contributes to EMT in ovarian cancer cells, it was previously found that GEP100 activated an Arf6 pathway with ASAP1 serving as an effector via receptor tyrosine kinases (RTKs), thus activated beta1 integrins and disrupted E-cadherin-based adhesion and promoted EMT in breast cancer (17). Arf6-ASAP1-EPB41L5 axis is another pathway to contribute to ASAP1-mediated EMT (18).…”
Section: Discussionmentioning
confidence: 99%